Modified Transhumeral Amputation: A Case Report. Issue 2 (25th April 2022) - Stanovski, Alexandra; Raviv, Dror; Azraq, Yusef; Diment, Judith; Olshinka, Noam; Or, Omer
Abstract : Case: A 7-year-old boy presented with osteosarcoma of the ulna that required a transhumeral amputation. The patient completed neoadjuvant chemotherapy before surgery. To prevent bone overgrowth and improved prosthetic fitting, a modified amputation was performed with acute shortening and distal epiphysis preservation. Conclusion: In this modified amputation, bone overgrowth was not seen and repeated surgeries for stump shaping were prevented. The modified technique enabled length for the prosthetic elbow and a wide stump for better fitting. In cases of transhumeral amputation in children, the modified technique should be considered.